Let’s Give Opportunism the Proper Back Seat - Lumineau, Fabrice; Verbeke, Alain (Academy of Management Review, 2016)
Nicolai Foss and Libby Weber (2016) propose to augment the micro-foundations of transaction cost economics (TCE) through enriching the bounded rationality concept. They argue that psychological frames and biases, when linked to different hierarchical forms, may give rise to differential, costly conflicts. In their view, such conflicts are entirely rooted in bounded rationality, as opposed to opportunism. In this contribution to the Academy of Management Review Dialogue Section, we raise three issues, which somewhat challenge Foss and Weber’s perspective on how to extend TCE, and we suggest an alternative path forward, thereby indeed giving opportunism ‘the proper back seat.’